A new split Hopkinson tensile bar design - Gerlach, R; Kettenbeil, C; Petrinic, N (2012)
This work presents a new design for a split Hopkinson tensile bar (SHTB) as well as generated representative experimental results. The new design uses a U shaped striker bar as projectile and addresses several shortcomings of classical SHTB designs using hollow striker bars. The results presented show that the non-symmetrical striker bar is capable of generating a clean and virtually oscillation free square pulse signal five times longer than typically achieved by classical striker tubes, whilst at the same time offering superior signal quality. Due to the longer stress pulse duration, the new SHTB design allows for the characterisation of materials at strain rates that were difficult to achieve for hydraulic testing machines and classical striker tube based SHTB designs. In addition, the developed SHTB is based on a simple and modular design and allows for a wide range of pulse shaping methodologies to be applied. Therefore, materials requiring different input stress pulse shapes, such as square (ductile), trapezoid or triangular (brittle), can be experimentally characterised at a large range of strain rates. © 2012 Elsevier Ltd. All rights reserved.